Implementasi Community Based Correction dalam Program Asimilasi Narapidana di Lembaga Pemasyarakatan - Subroto, Mitro; Zalukhu, Yeremia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of the assimilation program within the correctional system in Indonesia, particularly in the context of Community-Based Corrections that involve community participation. Indonesia's correctional system has undergone significant transformation, shifting from a punitive approach to one focused on rehabilitation and the reintegration of prisoners into society. The assimilation program is a critical phase in rehabilitation, allowing prisoners to gradually adapt to social life outside the correctional facility. This research uses a qualitative method with a descriptive approach, collecting data through literature studies, legal documents, and an analysis of psychological and sociological theories to understand the dynamics of assimilation. The findings of the study indicate that although the assimilation program provides opportunities for prisoners to reform and develop skills, its implementation faces several challenges, including overcrowding in correctional facilities, societal stigma, and undisciplined behavior from the prisoners. The success of this program requires synergy between correctional institutions, the community, and the prisoners themselves to achieve effective social reintegration and reduce the risk of recidivism